2013
DOI: 10.1128/mbio.00595-12
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Next Eye Pathogen: Analysis of a Novel Adenovirus

Abstract: For DNA viruses, genetic recombination, addition, and deletion represent important evolutionary mechanisms. Since these genetic alterations can lead to new, possibly severe pathogens, we applied a systems biology approach to study the pathogenicity of a novel human adenovirus with a naturally occurring deletion of the canonical penton base Arg-Gly-Asp (RGD) loop, thought to be critical to cellular entry by adenoviruses. Bioinformatic analysis revealed a new highly recombinant species D human adenovirus (HAdV-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 47 publications
4
43
0
1
Order By: Relevance
“…After primary binding of the fiber knob to its host cell receptor, the RGD motifs on the five-sided penton base capsomer bind to host cellular integrins to mediate endocytosis of the virus (42)(43)(44)(45). We previously showed that the two corresponding hypervariable regions of the penton base open reading frame frequently undergo homologous recombination (14,46), and we have suggested that penton base hypervariable regions may be important to viral pathogenesis (47). Our proteotyping analysis showed that the two hypervariable loops of the penton base protein of the EKC virus HAdV-D56 and the non-EKC virus HAdV-D9 are shared, as was previously shown (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After primary binding of the fiber knob to its host cell receptor, the RGD motifs on the five-sided penton base capsomer bind to host cellular integrins to mediate endocytosis of the virus (42)(43)(44)(45). We previously showed that the two corresponding hypervariable regions of the penton base open reading frame frequently undergo homologous recombination (14,46), and we have suggested that penton base hypervariable regions may be important to viral pathogenesis (47). Our proteotyping analysis showed that the two hypervariable loops of the penton base protein of the EKC virus HAdV-D56 and the non-EKC virus HAdV-D9 are shared, as was previously shown (10).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tested whether HAdV-D9, with an alanine at fiber knob amino acid 240 similar to the case for EKC viruses, would confer corneal epithelial cell tropism. To perform these studies, we used THE cells, which were previously shown to accurately recapitulate corneal tropism for EKC-associated viruses within HAdV-D (12,37,47). We compared HAdV-D9 entry and early gene expression with those of the EKC viruses HAdV-D37 and -D56.…”
Section: Discussionmentioning
confidence: 99%
“…Switching of the hexon variable regions to a low seroprevalence epitope of HAdV-48 (37) and producing the novel combination of the epitope-containing capsid proteins, represented as P65H48F60, may have increased the success rate of host infection by HAdV_Chiba_E086/2012 since the low seroprevalence indicates that only a small number of hosts have experienced HAdV-48-like viruses. The change to the HAdV-GT60-like fiber may have altered the tropism of this virus from bronchoalveolar (as in HAdV-GT59) (6) to ocular (34). If this virus is an adaptive form, it would have the potential to cause epidemic ocular infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally isolated from a respiratory infection, an experimental study has suggested that HAdV-GT60 may have a potential corneal tropism (34). In addition, the fiber knob has been reported to mediate the attachment of the virus to the receptor on the host cell (35,36), thus implying that the fiber is a determinant of tissue tropism of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Además, pueden comprometer los sistemas gastrointestinal, ocular, renal, entre otros, (3) con billones de personas infectadas a nivel mundial . (4,5) Comprenden 65 genotipos (HAdV-1 a HAdV-65) , de los cuales los primeros 51 tipos fueron caracterizados en base al tipo específico de (6,7) neutralización mediada por antisuero y los demás fueron designados por análisis bioinformático de (4) secuencias . Los genotipos se agrupan en siete (8) especies, denominadas HAdV-A a HAdV-G .…”
Section: Introductionunclassified